Like Any Other Woman The Lived Experience of Gynaecological Cancer - Saorsa, Jac (Cardiff University Press, 2019)
"Like Any Other Woman speaks to the suffering that cancer causes, and to the profound human experience of renegotiating the physical and emotional balance between sickness and health when that balance is tipped by the onset of disease. A profound and moving collaboration between an artist and a young woman who has endured the impact of a cancer diagnosis and its consequences, this is not a book about the cancer itself, the medical world of causes, symptoms, interventions and treatment regimes. It is rather about what it feels like when all sense of normality, all the expectations of a future that accompany good health, suddenly become submerged in degrees of suffering that impact both on the individual and on the people who care for and about her. Like Any Other Woman is illustrated with original artwork by Jac Saorsa, taken from the Drawing Women's Cancer project."